Functional Analysis of Ubie Frozen Food as a Snack Rich in Antioxidants and Anthocianins with The Best Processing Technology Innovation - Azizah, Nuraini; Anggia, Malse; Ulanda, Febri (Indonesian Journal of Food Technology, 2024)
The presence of anthocyanin compounds as a source of natural antioxidants in purple sweet potatoes is quite interesting to study considering the many benefits of anthocyanin content. As public awareness of the importance of healthy living increases, consumer demands for food are also increasingly shifting. This research aims to determine the chemical characteristics and assess the anthocyanin content and antioxidant content as well as determine the panelists' preferences for purple sweet potato products prepared using the steamed and boiled methods. The best antioxidant content is found in sweet potatoes using the boiled method, namely 743.97 ± 9.59 ppm, the best anthocyanin content is found in sweet potatoes using the steamed method, namely 50.00 ± 0.033 mg/100g. The chemical analysis carried out was water content and ash content. The lowest water content was in the steamed method, namely 27.24% and the lowest ash content test was found in sweet potatoes using the steamed method, namely 0.32%. The organoleptic test was carried out using a preference test with 25 panelists. It was found that the results of the test for the best taste and aroma were found in products using the steamed method and the best color and texture were found in products using the boiled method.